2023
DOI: 10.3390/foods12050965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic Pre-Treatment on Oat Flakes Protein Recovery and Properties

Abstract: Oats are considered an exceptional source of high-quality protein. Protein isolation methods define their nutritional value and further applicability in food systems. The aim of this study was to recover the oat protein using a wet-fractioning method and investigate the protein functional properties and nutritional values among the processing streams. The oat protein was concentrated through enzymatic extraction, eliminating starch and non-starch polysaccharides (NSP), treating oat flakes with hydrolases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Amino acid composition of extruded and unextruded DDGS is shown in Fig. 2(B) and Table 4, the total amino acid (TAA) did not change significantly ( P > 0.05), and the composition of essential amino acid (EAA) did not change significantly ( P > 0.05), which was congruent with the results of Sargautis et al 21 . Extrusion puffing had no significant effect on the amino acid composition of DDGS, indicated that the extrusion puffing of DDGS is a relatively loose process, which supported the research results of Boakye et al 22 .…”
Section: Resultssupporting
confidence: 89%
“…Amino acid composition of extruded and unextruded DDGS is shown in Fig. 2(B) and Table 4, the total amino acid (TAA) did not change significantly ( P > 0.05), and the composition of essential amino acid (EAA) did not change significantly ( P > 0.05), which was congruent with the results of Sargautis et al 21 . Extrusion puffing had no significant effect on the amino acid composition of DDGS, indicated that the extrusion puffing of DDGS is a relatively loose process, which supported the research results of Boakye et al 22 .…”
Section: Resultssupporting
confidence: 89%
“…However, even at the extreme measured values, the solubility was significantly lower than expected. Similar results were obtained via enzymatically extracting oat protein from oat flakes with subsequent separation of suspended solids and washing [ 58 ]. Despite introducing other raw materials, such as oat flakes, the oat protein resulted in relatively similar solubility (see Figure 2 ).…”
Section: Resultssupporting
confidence: 77%
“…Oats are rich in protein (12-20%) [18,19], which makes them an important source of bioactive peptides. Oat-derived peptides have antimicrobial [20] and metal-chelating [21] effects.…”
Section: Introductionmentioning
confidence: 99%